2015
DOI: 10.1021/jf506118j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Fat Diet on Hepatic Proteomics of Hamsters

Abstract: A high-fat diet contributes to the etiology of metabolic diseases. As the liver plays a crucial role in metabolism, an insight into the hepatic proteomics will help to illustrate the physiological effect of a high-fat diet. Fourteen nine-week old male Syrian hamsters were maintained on either control (C) or high-fat (HF) diets (0.2% cholesterol +22% fat) for 8 weeks. Hamsters were chosen because they show close similarity to human lipid metabolism. At the end of study, blood and livers were collected for analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 57 publications
(126 reference statements)
2
17
0
1
Order By: Relevance
“…This was in agreement with increased activities of glycolytic enzymes, in particular pyruvate kinase, a phenomenon also reported by others [50,51]. Decreased protein levels of several TCA cycle enzymes (ACO2, OGDH, SUCLA2, and SUCLG1), all of them catalyzing reactions downstream of citrate, suggest that TCA cycle activity might have been limited upon glucose and fructose feeding, favoring the translocation of citrate to the cytosol for lipogenesis [52]. Importantly, most of these effects were more profound in response to fructose compared with glucose.…”
Section: Discussionsupporting
confidence: 89%
“…This was in agreement with increased activities of glycolytic enzymes, in particular pyruvate kinase, a phenomenon also reported by others [50,51]. Decreased protein levels of several TCA cycle enzymes (ACO2, OGDH, SUCLA2, and SUCLG1), all of them catalyzing reactions downstream of citrate, suggest that TCA cycle activity might have been limited upon glucose and fructose feeding, favoring the translocation of citrate to the cytosol for lipogenesis [52]. Importantly, most of these effects were more profound in response to fructose compared with glucose.…”
Section: Discussionsupporting
confidence: 89%
“…After 20 weeks, the golden hamster model of metabolism disorder induced by HFD feeding was established, with substantially increased serum levels of biochemical indicators (including TG, CHO, LDL-C, and others). The model was very appropriate because golden hamsters respond consistently to dietary modulation and, compared with the profiles of other rodents, showed a close similarity to human lipoprotein profiles ( Liao et al, 2015 ). In this paper, we found that supplemental AEM (1,200 mg/kg) did not alter food intake but significantly prevented the increased in body weight, liver weight, and fat weight that occurred in golden hamsters fed a HFD for 20 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as diet, hormones, and numerous transcription factors and nuclear receptors are known to regulate ARG1 expression. For instance, hamsters, which have a lipid metabolism similar to humans, when fed with a high‐fat diet exhibited suppression of several urea cycle enzymes including ARG1 (Liao, Lin, & Kuo, ). In fetal rat, cortisol has been shown to stimulate liver ARG1 after an intraperitoneal injection (Husson & Vaillant, ).…”
Section: Variantsmentioning
confidence: 99%